Occupational Mobility of Routine Workers - Terhi Maczulskij (The Research Institute of the Finnish Economy (ETLA), 2021)
This paper analyzes whether occupational polarization takes place within workers or due to changes in the composition of workers by using comprehensive panel data from Finland. The decomposition analysis shows that the decrease in mid-level routine occupations and the simultaneous increase in high-level abstract occupations is largely a within-worker phenomenon. In contrast, the share of low-skilled nonroutine manual tasks has largely increased through entry dynamics. Data on plant closures are used to identify involuntary separations from routine occupations. These results demonstrate a strong, uneven adjustment pattern, with routine cognitive workers being more able to move to abstract tasks and adjust with smaller wage costs than routine manual workers.
Keywords: J23; J62; 330; Job market polarization; Routine manual; Routine cognitive; Decomposition; Occupational mobility; Displacement